The Relationship Between Creed and Ethics In Islamic Philosophy (Analysis Of Imam Al-GhazalI'S Thought) - Lukman; Sopiyan, Wawan (El-Ghiroh : Jurnal Studi Keislaman, 2026)
This study aims to examine the relationship between faith and ethics in Islamic philosophy through a qualitative study of Al-Ghazali's thought. Using textual analysis of primary works, particularly the Ihya' Ulumuddin (The Islamic Theology), as well as a secondary literature review, this study investigates how the concept of faith (aqidah) shapes and reinforces ethical norms and behavior in the context of Islamic spirituality. An in-depth analysis of classical texts reveals that the integration of theological beliefs and ethical values ??is a crucial foundation for the formation of the moral order and social life of Muslims. The research findings demonstrate that Al-Ghazali's thought offers a holistic synthesis, in which the principle of tawhid serves not only as a foundation for faith but also as a primary driver in the development of personal and social ethics. These findings impact contemporary understanding of the dynamics of the interaction between religious aspects and morality and open up space for interdisciplinary dialogue between theology and philosophy.